Industries Based on the Petrochemical Industry in Iraq-Plastics Industry as a Model - Mohammed Abdel Rahman, Farah; Kareem Buraihi, Fares (Journal of Economics and Administrative Sciences, 2023)
This study came to discuss the subject of industries dependent on petrochemical industries in Iraq (plastic as a model) during the period 2005–2020, and the study concluded that the plastic industries contribute to areas of advancement and progress and opportunities to deal efficiently with the challenges posed by the new variables, the most important of which is the information revolution. communications and trade liberalization, and this is what contributes to the competitiveness of these industries. And because the petrochemical industry in Iraq has an active role in establishing plastic industrial clusters and clusters of micro, small, and medium industries by providing the necessary feedstock for these industries in various fields and industrial sectors, such as plastic packaging industries and building, And the industries feeding the automobile industry, textiles, machinery and equipment manufacturing, and other industries, depending on the availability of various petrochemical products and feedstocks. The study recommended developing strategies and approving medium and long-term development plans through which results can be benefited from in the field of developing small, medium, and micro industries, as well as coordination and cooperation between agencies. , and the bodies concerned with the development of small and medium enterprises in the Arab countries, encouraging the establishment of projects for small and medium industries, reviewing policies and legislation, and updating them to ensure facilitating financing procedures and encouraging and stimulating the participation of the private sector in the development of small and medium enterprises in addition to the government sector. Paper type: Research paper